Social Justice and Human Rights: A Legal Perspective - Setiawan , Andri Herman; Sunandar, Firman Nurdiansyah; Fajar, Ahmad (Politeknik Siber Cerdika Internasional, 2025)
Social justice and human rights are fundamental principles that shape the legal and political frameworks of modern societies. This study explores the legal dimensions of social justice and human rights by examining their conceptual foundations, international legal instruments, and practical implications in national legal systems. The research delves into the interplay between human rights law and social justice theories, highlighting the role of legal institutions in promoting equality, non-discrimination, and access to justice. Furthermore, it analyzes contemporary challenges such as economic disparities, marginalized communities, and state obligations under international human rights treaties. Through a doctrinal legal approach, this study reviews relevant legal frameworks, case law, and scholarly debates to provide a comprehensive understanding of how social justice is realized through the law. The findings underscore the necessity of a rights-based legal framework to address structural inequalities and ensure the protection of fundamental freedoms for all individuals. This research contributes to the ongoing discourse on legal mechanisms that enhance social justice within the broader context of human rights law.